Probiotics Supplementation Therapy for Pathological Neonatal Jaundice: A Systematic Review and Meta-Analysis - Chen, Zhe; Zhang, Lingli; Zeng, Linan; Yang, Xiaoyan; Jiang, Lucan; Gui, Ge; Zhang, Zuojie (Frontiers in Pharmacology, 2017)
Background: Neonatal jaundice is a relatively prevalent disease and affects approximately 2.4% to 15% newborns. Probiotics supplementation therapy could assist to improve the recovery of neonatal jaundice, through enhancing immunity mainly by regulating bacterial colonies. However, there is limited evidence regarding the effect of probiotics on bilirubin level in neonates. Therefore, this study aims at systematically evaluating the efficacy and safety of probiotics supplement therapy for pathological neonatal jaundice. Methods: Databases including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan Fang Database (Wan Fang), Chinese Biomedical Literature Database (CBM), VIP Database for Chinese Technical Periodicals (VIP) were searched and the deadline is December 2016. Randomized controlled trials (RCTs) of probiotics supplementation for pathological neonatal jaundice in publications were extracted by two reviewers. The cochrane tool was applied to assessing the risk of bias of the trials. The extracted information of RCTs should include efficacy rate, serum total bilirubin level, time of jaundice fading, duration of phototherapy, duration of hospitalization, adverse reactions. The main outcomes of the trials were analyzed by Review Manager 5.3 software. The relative risks (RR) or mean difference (MD) with a 95% confidence interval (CI) was used to measure the effect. Results: 13 RCTs involving 1067 neonatal with jaundice were included in the meta-analysis. Probiotics supplementation treatment showed efficacy [RR: 1.19, 95% CI (1.12, 1.26), P < 0.00001] in neonatal jaundice. It not only decreased the total serum bilirubin level after 3day [MD: -18.05, 95% CI (-25.51, -10.58), P<0.00001], 5day [MD: -23.49, 95% CI (-32.80, -14.18), P<0.00001], 7day [MD: -33.01, 95% CI (-37.31, -28.70), P<0.00001] treatment, but also decreased time of jaundice fading [MD: -1.91, 95% CI (-2.06, -1.75), P < 0.00001], as well as the duration of phototherapy [MD: -0.64, 95% CI (-0.84, -0.44), P < 0.00001] and hospitalization [MD: -2.68, 95% CI (-3.18, -2.17), P < 0.00001], when compared with the control group. Additionally, no serious adverse reaction was reported. Conclusion: This meta-analysis shows that probiotics supplementation therapy is an effective and safe treatment for pathological neonatal jaundice.